Plant-Morphing Strategies and Plant-Inspired Soft Actuators Fabricated by Biomimetic Four-Dimensional Printing: A Review - Ren, Luquan; Li, Bingqian; Wang, Kunyang; Zhou, Xueli; Song, Zhengyi; Ren, Lei; Liu, Qingping (Frontiers in Materials, 2021)
For prey, seeding, and protection, plants exhibit ingenious adaptive motions that respond autonomously to environmental stimuli by varying cellular organization, anisotropic orientation of cellulose fibers, mechanical instabilities design, etc. Notably, plants do not leverage muscle and nerves to produce and regulate their motions. In contrast, they harvest energy from ambient environment and compute through embodied intelligence. These characteristics make them ideal candidates for the application in self-morphing devices. 4D printing is a bottom-up additive manufacturing method that builds objects with the ability to change shape/properties in a predetermined manner. A versatile motion design catalogue are required to predict the morphing processes and final states of the printed parts. This review summarizes the morphing and actuation mechanisms of plants, and concludes the recent development of 4D printed smart materials inspired by the locomotion and structures of plant systems. We provide the analyses of the challenges and envisions of biomimetic 4D printing, hoping to boost its application in soft robotics, smart medical devices, and smart parts in aerospace, etc.